Delayed completion of pneumococcal conjugate vaccination among children 4–48 months in rural Uganda: a socio-demographic inquiry - Herbert Malemo; Andrew Tamale; Paul Kakwangire; Matthew C. Igwe; Dickens R. Mwine; Isa Asiimwe; Solomon A. Mbina; Mary G. Abalinda (BMC Pediatrics)
Abstract In spite of the commendable global Pneumococcal Conjugate Vaccine (PCV) coverage in the last two decades, completion and timeliness of receipt of all the required doses are still below target. In Uganda, the 3 + 0 PCV regimen has been reported to have a steady decline in the completion rate and the reasons for the delayed completion are unidentified. This study aimed at assessing the influence of socio-demographic factors on delayed PCV completion among young children. A cross-sectional study design among 362 child/caretakers pairs in Bugongi Town Council was employed. Using stratified sampling – Allocation Proportional to Size, data was collected using pretested questionnaires; entered and analysed using STATA v14 and significant statistical association was considered at P ≤ 0.05. Of the 362 children, majority (53.87%) were boys. Child mean age was 25.1 ± 14.3 months. 87.6% caretakers were females and majorities of them were aged 20–29yrs (47.8%), peasant farmers (79.8%), married (90.6%), attained primary education (63.5%) and earned average monthly income of UGX 10,000 – UGX 50,000 (41.4%). Of the 362 children, 92 (25.4%) had delayed to receive their PCV-3 doses. Only boy child [cOR = 1.65, (95%CI: 1.03–2.66); P = 0.039) and caretaker’s age 30–39 [cOR = 2.12 (95%CI: 1.06–4.24); P = 0.033) showed statistical significance at bivariate analysis. The multivariate model found parent’s age 20–29 years [aOR = 2.39 (1.14–5.01); P = 0.021] and 30–39 years [aOR = 2.51 (1.16–5.45); P = 0.020] as positively associated factors whereas being married [aOR = 0.20 (0.04–0.96); P = 0.044] was the only negatively associated factors to delayed completion of PCV vaccination among young children. Among children who complete the last dose of PCV vaccination, a considerable proportion are actually receiving it late which may result into eventual failure to curb the targeted pneumococcal infections. Thus, concerted efforts in terms of sensitization are un-doubtfully desired especially among caretakers aged 20–39 years as well as those who are not married.